Effect of Supplemental Corn Dried Distillers Grains with Solubles Fed to Beef Steers Grazing Native Rangeland during the Forage Dormant Season - Murillo, M (Asian-Australasian journal of animal sciences, 2016)
Two experiments were conducted to evaluate the effects of the level of corn dry distillers grains with solubles (CDDGS) supplementation on growing performance, blood metabolites, digestion characteristics and ruminal fermentation patterns in steers grazing dormant forage. In Exp. 1, of growth performance, 120 steers (204±5 kg initial body weight [BW]) were distributed randomly into 3 groups (each of 40 steers), which were provided with the following levels of CDDGS supplement: 0%, 0.25%, or 0.50% BW. All groups of steers were grazed for 30 days in each of 3 grazing periods (March, April, and May). Approximately 1,000 ha of the land was divided with electric fencing into 3 equally sized pastures (333 ha in size). Blood samples were collected monthly from 20 steers in each grazing group for analysis of glucose (G), urea-nitrogen (UN) and non-esterified fatty acids. Final BW, average daily gain (ADG) and supplement conversion (CDDGS-C) increased with increasing levels of CDDGS supplementation (p<0.05).The CDDGS supplementation also increased the plasma G and UN concentrations (p<0.05). In Exp. 2, of digestive metabolism, 9 ruminally cannulated steers (BW = 350±3 kg) were distributed, following a completely randomized design, into groups of three in each pasture. The ruminally cannulated steers were provided the same levels of CDDGS supplementation as in the growing performance study (0%, 0.25%, and 0.50% BW), and they grazed along with the other 40 steers throughout the grazing periods. The dry matter intake, crude protein intake, neutral detergent fiber intake (NDFI), apparent digestibility of dry matter (ADDM), crude protein (ADCP) and neutral detergent fiber (ADNDF) increased with increasing levels of CDDGS supplementation (p<0.05). The ruminal degradation rates of CP (kdCP), NDF (kdNDF) and passage rate (kp) also increased with increasing levels of CDDGS supplementation (p<0.05). Ruminal ammonia nitrogen (NH3-N) and propionate concentrations also increased with increasing levels of CDDGS supplementation (p<0.05). However, acetate concentrations decreased with increasing levels of CDDGS supplementation (p<0.05). Liquid dilution rate increased with increasing levels of CDDGS supplementation but ruminal liquid volume decreased (p<0.05). On the basis of these findings, we can conclude that CDDGS supplementation enhanced the productive performance of cattle grazing native rangeland without negatively affecting forage intake, glucose and urea-nitrogen blood concentrations, ruminal degradation and ruminal fermentation patterns